Direct modulus measurement of single composite nanofibers of silk fibroin/hydroxyapatite nanoparticles. (18th January 2016) - Yang, Dasom; Kim, Hyunryung; Lee, JiYong; Jeon, Hojeong; Ryu, WonHyoung
Abstract: When cells are populated in fibrous scaffolds, the mechanical strength of individual nanofibers has significant influence on cell behaviors such as cell attachment, proliferation, differentiation, and protein expressions. However, analysis of mechanical property of tissue scaffolds has been rather limited to macroscopic scaffolds than local cell-scale force field of scaffolds. Silk fibroin (SF) has been frequently utilized in a form of nanofibers as promising tissue scaffolding material. However, due to difficulty of processing composite nanofibers with uniformly mixed SF and nanoparticles, mechanical analysis of SF-based composite nanofibers has not been investigated yet. In this study, we fabricated "composite" nanofibers of silk fibroin (SF) with hydroxyapatite (HAp) up to 40 wt% that were uniformly dispersed in the SF nanofibers. Their mechanical moduli and dependency on the content of HAp nanoparticles were analyzed using three point bending with tipless AFM cantilever (AFM-TPB). The composite single nanofibers became stiffer with higher content of HAp nanoparticles up to 20 wt% of HAp. Further addition of HAp nanoparticles reduced the mechanical strengths of the composite single nanofibers similarly to macroscale electrospun scaffolds. DSC and XRD analysis revealed that the crystallinity of SF increased up to 20 wt% and became saturated at higher contents of HAp nanoparticles. It was also noticeable that the single composite nanofibers had two orders of magnitude higher mechanical moduli than macro scaffolds samples. Graphical abstract: